NILAI MORAL DARI ASPEK HUBUNGAN MANUSIA DENGAN MANUSIA DALAM KUMPULAN CERITA RAKYAT DAERAH JAMBI KARYA THABRAN KAHAR - Abdoel Gafar; Nurul Sarah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The research is aimed at describing the moral value aspects of human-to-human relationships in Kumpulan Cerita Rakyat Daerah Jambi by Thabran Kahar. The moral value consists of aspects (1) caring for others, (2) helping, (3) deliberation, (4) living together, (5) forgiving, (6) keep on promise, (7) appreciating others. This research includes descriptive qualitative types. Qualitative descriptive describes an event with words or images of objects with actual circumstances. The data sources in this research are words, sentences, quotations or expressions that can be found in the dialogue of the characters in Kumpulan Cerita Rakyat Daerah Jambi by Thabran Kahar. Based on the results of this research, it can be concluded that aspects of the moral value of human relationships with other human beings are contained in the Kumpulan Cerita Rakyat Daerah Jambi by Thabra Kahar. The data showed that there are 60 expressions that are divided into seven aspects of moral values including: caring for each other as many as 14 quotations, please help as many as 12 quotations, deliberation as many as 9 quotations, living together as many as 8 quotations, forgiving as many as 6 quotes, keep on promise as many as 4 quotations, and respect others as many as 7 quotations.